IDENTIFIKASI BAHAYA DAN PENILAIAN RISIKO PENGUJIAN KENDARAAN BERMOTOR DI UPT PENGUJIAN KENDARAAN BERMOTOR DINAS PERHUBUNGAN KOTA BALIKPAPAN - Adi Wahyudi; Komeyni Rusba; James EA Liku (Media Bina Ilmiah, 2023)
The process of carrying out motorized vehicle testing at the Technical Implementation Unit (UPT) of the Balikpapan Transportation Service, test officers work every day with a high level of risk, in daily life vehicle test officers are always directly exposed to air pollution, noise, heat, exposure to toxic exhaust gases from vehicles, facing various possible risks ranging from mild risk to high risk. The aim of this research is; Want to carry out hazard identification and risk assessment in the process of testing motor vehicles from the beginning to the end of the work safety and health of the test officers. This study uses the HIRARC method. This research data uses 2 (two) types, namely primary data and secondary data. The primary data collection method is by interviewing the examiner and Plt. Head of UPT and perform documentation. While secondary data is done by way of literature review. The level of risk (risk level) that arises from defining the criteria of likelihood (likelihood) and level of severity (severity). Research result; (1) From the likelihood criteria, it shows that the average occurrence of work accidents is low (score 2) accidents rarely occur, probably 1 (one) time in 5 years. (2) From the criteria of severity, it shows that the average long-term severity is vulnerable (score 4) to risks that can actually occur in the long term, namely, chronic respiratory disorders, caused by frequent inhalation of toxic exhaust gases, illness in part of the spine, which is caused by work posture factors sitting, squatting which is repeated continuously for 7 hours/day. Based on the HIRARC theory, the intersection of likelihood score 2 (two) and severity score 4 (four) is in the high risk zone.